Analisis Pengaruh Dana Perimbangan dan Dana Otonomi Khusus Terhadap Pertumbuhan Ekonomi di Kabupaten Supiori - Vita Nurrohmah; Halomoan Hutajulu (Jurnal Kajian Ekonomi dan Studi Pembangunan, 2024)
This study aims to analyze the influence of Dana Perimbangan and Dana Otonomi Khusus (Special Autonomy Funds) on economic growth in Supiori Regency. Dana Perimbangan, which consists of the General Allocation Fund (DAU), Revenue Sharing Fund (DBH), and Special Allocation Fund (DAK), along with Special Autonomy Funds (Otsus), are transfers from the central government to support regional development and welfare. This research uses a quantitative approach with secondary data obtained from the Central Bureau of Statistics (BPS) and the Regional Financial and Asset Management Agency (BPKAD) of Supiori Regency for the period 2010-2023. Multiple linear regression analysis was used to examine the influence of the independent variables on the dependent variable, namely economic growth, which is measured by the Gross Regional Domestic Product (GRDP).The results of the study indicate that Dana Perimbangan has a positive and significant impact on economic growth in Supiori Regency, with an increase in Dana Perimbangan significantly raising the region's GRDP. Conversely, Special Autonomy Funds have a negative and significant impact on economic growth, indicating that increased Otsus funds do not optimally contribute to local economic growth. Collectively, Dana Perimbangan and Special Autonomy Funds have a significant influence on economic growth in Supiori Regency. These findings emphasize the need for improving the effectiveness of the allocation and management of Special Autonomy Funds to maximize their contribution to regional economic development. Keywords: Economic Growth, Balancing Fund, and Special Autonomy Fund